Toward Measuring Household Vulnerability to Income Poverty in the Philippines - Jose Ramon G. Albert; Lilia V. Elloso; Andre Philippe Ramos (Philippine Institute for Development Studies (PIDS), 2007)
Concomitant to the analysis of poverty is the measurement of vulnerability. Estimates of household vulnerability to income poverty are developed using a modified probit model that considers volatilities in income as being explained by some household characteristics. Resulting vulnerability estimates are found to be higher than poverty rates, suggesting that policy interventions will have to be developed to minimize the risk households face in becoming income poor, or at least help them in mitigating the impact of their becoming poor.
Keywords: 330; vulnerability; poverty; Soziale Lage; Privater Haushalt; Risiko; Armut; Messung; Philippinen